Demagnetizing fields in all-optical switching. (14th December 2017) - Hoveyda, F; Hohenstein, E; Judge, R; Smadici, S
Abstract: A model of demagnetizing fields and micromagnetic simulations are applied to examine the evolution of a demagnetized cylinder. In addition to three expected final magnetic structures, a fourth switched state is obtained over a range of magnetic energy densities. The switched state is absent when demagnetizing fields are neglected. The connection to all-optical switching of materials with perpendicular magnetic anisotropy is discussed.